A Qualitative Analysis of the ISKCON Movement in South Africa - Bishop, James (Department of Religious Studies, 2023)
This thesis explores the International Society for Krishna Consciousness (ISKCON) movement in South Africa. I employ qualitative analysis and use David Chidester's theory of symbolic exchange to analyze contestations over symbols between ISKCON devotees and proponents of competing perspectives in the contemporary South African context. I analyze the “battlefield” of symbol contestation and its many participants who wish to “own” sacred symbols, alienate others from this ownership, and how symbols are appropriated to serve specific “interests”. Evaluating discourses and contestations over symbols clarify central tenets in the ISKCON movement's worldview, what the religion seeks to communicate, to whom it communicates, the strategies it employs, and its interests that are served.